Optimization of Heterogeneous Data in Sensor Networks to Industrial Internet - Kniess, Janine (Anais Estendidos do Latin-American Symposium on Dependable and Secure Computing (LADC); 2023: Anais Estendidos do XII Latin-American Symposium on Dependable Computing, 2023)
The growth of applications in the context of the Industrial Internet (IIoT) has resulted in new requirements to meet the heterogeneity of sensors used in monitoring industrial assets. Data transmission is a fundamental activity for IIoT applications. However, an efficient network transmission must care about consumption of available resources. These are the aims of the Approach for Heterogeneous Data Reduction in Wireless Sensors Networks (Δ HEAR), presented in this paper. Applying Dispersion Analysis, Data Aggregation and Lossless Compression models to reduce heterogeneous data transmitted in sensor networks in a distributed way. Performance evaluation results on the Cooja simulator confirm the effectiveness of approach in reduces sensor data and energy consumption.